Association between ambient particulate matter and respiratory health among schoolchildren in Dar es Salaam city, Tanzania: a cross-sectional study - Justus Kamara; Stephen Kishinhi; Asinta Manyele; Happiness Saronga; Jovine Bachwenkizi (BMC Public Health)
Abstract Background Urbanization and industrial activities have significantly contributed to the deterioration of air quality, with ambient particulate matter (PM2.5 and PM10) posing a major public health concern in most cities of developing countries. The impact of these pollutants on respiratory health, particularly that of schoolchildren, has remained inadequately studied. Objective This study aimed to determine the level of ambient particulate matter (PM2.5 and PM10) and its association with respiratory symptoms among school children in Dar es Salaam, Tanzania. Methods We conducted a cross-sectional study targeting schoolchildren aged 9–16 to investigate the impact of air pollution on respiratory health. A sample of 427 children was selected through stratified random sampling, which combined primary and secondary data. Standardized questionnaires and air quality monitoring for PM exposure were used to collect data. Analysis methods included descriptive statistics, and logistic regression to elucidate the association between PM exposure and respiratory symptoms. Results The prevalence of respiratory symptoms among the schoolchildren was notably high, with 35.1% reporting coughing, 26.7% wheezing, 31.4% breathlessness, and 28.1% severe chest illness. Significant associations were found between proximity to pollution sources (OR = 3.4, 95% CI: 2.3–5.0, p < 0.001 for coughing; OR = 7.0, 95% CI: 2.9–17.2, p < 0.001 for wheezing; OR = 3.9, 95% CI: 2.3–6.6, p < 0.001 for breathlessness; OR = 6.4, 95% CI: 3.3–12.0, p < 0.001 for severe chest illness), household smoking (OR = 1.2, 95% CI: 1.02–1.4, p < 0.05 for wheezing; OR = 1.2, 95% CI: 1.01–1.4, p < 0.05 for severe chest illness), and the use of biomass for cooking (OR = 2.4, 95% CI: 1.4–4.0, p < 0.01 for wheezing; OR = 2.3, 95% CI: 1.4–3.8, p < 0.01 for severe chest illness) with the occurrence of respiratory symptoms. Ambient PM levels, particularly PM2.5 and PM10, exceeded WHO limits in several locations. WHO recommends PM2.5 levels below 5 µg/m3 and PM10 below 15 µg/m3, while Dar es Salaam recorded PM2.5 between 35–50 µg/m3 and PM10 between 75–100 µg/m3, significantly higher than recommended. Conclusion The study emphasizes the significant impact of air pollution on the respiratory health of schoolchildren in Dar es Salaam and calls for targeted interventions to reduce particulate matter exposure, particularly in high-risk urban areas of Dar es salaam, Tanzania.